Indigenous pathogen, Bipolaris sorokiniana (Sacc.) shoemaker as potential biocontrol of goosegrass [Eleusine indica (L.) gaertn.] - Ismail, Maizan (2019)
Goosegrass or Eleusine indica is a noxious weed in plantations, orchards, and farms in Malaysia. It listed as one of the 10 worst weeds of the world and to be the most destructive grass in oil palm plantations. Currently, farmers apply herbicides to control weeds in their farms. Unfortunately, a continuous use of some herbicides have resulted in herbicide resistance in some weed species. Biological control of weed using pathogens is one of the alternatives to control weeds being reported by researchers. Hence, the objectives of this study were, 1) to identify the potential indigenous plant pathogens to control E. indica; 2) to determine the pathogenicity of the plant pathogens towards E. indica; and 3) to evaluate the efficacy of the plant pathogens as a biocontrol agent for E. indica. Fungi associated with E. indica were isolated from diseased plants and identified as Bipolaris sorokiniana, Phoma herbarum, and Curvularia aeria. The fungi were tested and evaluated in a nursery to control Eleusine indica. The pathogenicity test showed that B. sorokiniana was more pathogenic to E. indica compared to P. herbarum and C. aeria. B. sorokiniana affected the growth of E. indica and caused dry weight loss, which was significantly lower than the dry weight loss of E. indica treated with P. herbarum and C. aeria, and the untreated control. Further screening of B. sorokiniana against 11 host plants showed that it had only caused localized lesion on leaves of the crop plants and very mild disease severity (10-20%), compared to the severe disease it had caused on E. indica (79%). Factors affecting the efficacy of B. sorokiniana were studied. Fungal growth was evaluated in four artificial media, namely Corn Meal Agar (CMA), Potato Dextrose Agar (PDA), V8 Agar (V8A), and Water Agar (WA), under three light durations. On PDA, the highest colony diameters were obtained without light intensity (4.21cm), as well as with 12 hours light intensity (4.56cm). B. sorokiniana with a concentration of 2 x 107 CFU/ml + 0.01% Tween 20, inoculated E. indica with severe damaged (100%) and it was concluded that the highest concentration of inoculum would give the highest disease severity to E. indica. High relative humidity resulted in high dispersal and disease severity development on E. indica. B. sorokiniana that was inoculated to E. indica and covered with polythene bags for 48 hours resulted in the highest disease severity. Two to three applications of treatment at 2-week interval recorded the highest percentage of disease severity. The infection was accelerated when the treatment application was started at 8 to 9 leaves stages of E. indica and the disease prolonged. The highest percentage of disease severity started from day- 5 after treatment until day-20 after treatment. The potential of B. sorokiniana as a biocontrol agent was studied under field conditions and chemical treatment (glyphosate) as negative control was used. The result showed that chemical control was effective in killing E. indica in the plot. In terms of biocontrol, the treatment of B. sorokiniana with a concentration of 2 x 107 + 0.01% Tween 20, sprayed three times at 2-week interval gave the highest rating of disease severity. The highest disease symptom was recorded as early as day-7 after this treatment compared to other biocontrol treatments, and more frequency of spraying showed a higher action of disease dispersal on E. indica. This treatment also resulted in the lowest dry weight (254g/plot) of E. indica, which signified an inhibition of its growth. In this experiment, the biocontrol showed no significant difference compared to chemical treatment, except that the chemical treatment reacted faster in controlling E. indica, while the biocontrol took more time to perform the task, yet was safer and more environmentally friendly. B. sorokiniana has the distinctive aspects of a good biocontrol agent.